2005
DOI: 10.1038/nn1596
|View full text |Cite
|
Sign up to set email alerts
|

FARP2 triggers signals for Sema3A-mediated axonal repulsion

Abstract: Sema3A, a prototypical semaphorin, acts as a chemorepellent or a chemoattractant for axons by activating a receptor complex comprising neuropilin-1 as the ligand-binding subunit and plexin-A1 as the signal-transducing subunit. How the signals downstream of plexin-A1 are triggered upon Sema3A stimulation, however, is unknown. Here we show that, in the presence of neuropilin-1, the FERM domain-containing guanine nucleotide exchange factor (GEF) FARP2 associates directly with plexin-A1. Sema3A binding to neuropil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
216
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(225 citation statements)
references
References 43 publications
6
216
2
Order By: Relevance
“…In addition, recent reports revealed that PI(4,5)P 2 acts as a second messenger and controls focal adhesion dynamics and actin cytoskeleton [57], both of which are critical for cell migration. In neuronal cells, inhibition of another isoform of PIP5K, PIPKIγ661, is required for Sema3A-induced axonal repulsion and growth cone collapse [42]. These data suggest that semaphorins may commonly utilize phospholipid-regulated signaling Figure 2 Anti-angiogenic signaling by Sema3E-plexin D1 in endothelial cells.…”
Section: Sema3ementioning
confidence: 98%
See 1 more Smart Citation
“…In addition, recent reports revealed that PI(4,5)P 2 acts as a second messenger and controls focal adhesion dynamics and actin cytoskeleton [57], both of which are critical for cell migration. In neuronal cells, inhibition of another isoform of PIP5K, PIPKIγ661, is required for Sema3A-induced axonal repulsion and growth cone collapse [42]. These data suggest that semaphorins may commonly utilize phospholipid-regulated signaling Figure 2 Anti-angiogenic signaling by Sema3E-plexin D1 in endothelial cells.…”
Section: Sema3ementioning
confidence: 98%
“…The molecular mechanisms by which Sema3A regulates integrins are not fully understood. From the studies in neuronal cells, it is likely that activation of plexin-A1 by Sema3A induces the intrinsic R-Ras GAP activity of Plexin-A1, thus resulting in R-Ras inhibition [16,42]. As R-Ras is known to sustain integrin activation, the inactivation of R-Ras by plexin-A1 may lead to the inactivation of integrins, thereby inhibiting integrinmediated cell adhesion.…”
Section: Sema3amentioning
confidence: 99%
“…In the nervous system, semaphorin-plexin signaling has been shown to mediate diverse neural functions by regulating GTPase activities and cytoplasmic/receptor-type protein kinases. 11,31,32 These plexin-mediated signals are involved in integrin-mediated attachment, 15,33,34 actomyosin contraction [35][36][37][38] and microtubule destabilization. [39][40][41] In addition, plexins can associate with different coreceptors in distinct tissues to allow semaphorins to exert pleiotropic functions.…”
Section: Semaphorins and Their Receptorsmentioning
confidence: 99%
“…Of particular interest is the recognition that the plexin intracellular region exhibits sequence similarity to Ras GTPase-activating proteins (Ras GAPs), representing the first example of a transmembrane receptor containing a GAP domain (6,7). R-Ras, a homologue of Ras involved in regulating cell adhesion and neurite outgrowth, is a substrate of the plexin GAP (8,9). Conversion of R-Ras into the GDP-bound inactive form by the plexin GAP leads to decreased activity of integrin and loss of cell adhesion, contributing to repulsive axon guidance.…”
mentioning
confidence: 99%